1970
DOI: 10.1152/ajplegacy.1970.218.6.1555
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of ADH release by the renin-angiotensin system

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
3

Year Published

1972
1972
1992
1992

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(76 citation statements)
references
References 0 publications
3
70
0
3
Order By: Relevance
“…A direct action of angiotensin I1 on free water reabsorption in the tubule has been recently demonstrated in dogs (15). However, it is known that angiotensin I1 enhances vasopressin release (6).…”
Section: Discussionmentioning
confidence: 99%
“…A direct action of angiotensin I1 on free water reabsorption in the tubule has been recently demonstrated in dogs (15). However, it is known that angiotensin I1 enhances vasopressin release (6).…”
Section: Discussionmentioning
confidence: 99%
“…Bonjour and Malvin (22) demonstrated that systemic administration of angiotensin II caused an increase in the level of plasma ADH, and Gagnon et al (9) provided evidence that ADH liberation from isolated neurohypophysis was increased by angiotensin II. Additional ly, although bradykinin given through the intracarotid artery route rather than intravenously was more effective in an increment of blood ADH concentrations, direct stimulation by the kinin of the pituitary was not observed (10).…”
Section: Discussionmentioning
confidence: 99%
“…In animals (Schmitt et al, 1981) or in man (Kimura et al, 1986), the natriuretic and diuretic effect of frusemide produces a decrease in plasma volume similar to the one observed after haemorrhage. As a consequence, AVP secretion is considerably enhanced by baroreceptors, mechanoreceptors (Ledsome et al, 1985), the renin-angiotensin system (Bonjour & Malvin, 1970) and the a-adrenergic system (Kimura et al, 1980;Paller & Linas, 1984;Brunner et al, 1983). …”
Section: Effects Of Lignocaine On Arginine-vasopressin Serum Levelsmentioning
confidence: 99%